NeoFLOT: Multicenter phase II study of perioperative chemotherapy in resectable adenocarcinoma of the gastroesophageal junction or gastric adenocarcinoma—Very good response predominantly in patients with intestinal type tumors. Issue 3 (25th February 2015) - Schulz, Christoph; Kullmann, Frank; Kunzmann, Volker; Fuchs, Martin; Geissler, Michael; Vehling‐Kaiser, Ursula; Stauder, Heribert; Wein, Axel; Al‐Batran, Salah‐Eddin; Kubin, Thomas; Schäfer, Claus; Stintzing, Sebastian; et al.
<x xml:space="preserve">Abstract</x> Perioperative treatment is a standard of care in locally advanced gastroesophageal cancer (GEC) (gastric adenocarcinoma and gastroesophageal junction (GEJ) adenocarcinoma). While preoperative treatment can be applied to the majority of patients, postoperative chemotherapy can be given only to a fraction. The NeoFLOT‐study therefore investigates the application of prolonged neoadjuvant chemotherapy (NACT). Patients with T3, T4, and/or node‐positive adenocarcinoma (GEC) were eligible for this multicenter phase II trial. NACT consisted of 6 cycles of oxaliplatin 85 mg/m2, leucovorin 200 mg/m2, 5‐fluorouracil 2600 mg/m2 and docetaxel 50 mg/m2 (FLOT) applied q 2 wks. Application of adjuvant chemotherapy was explicitly not part of the protocol. R0‐resection rate was evaluated as a primary endpoint. Of 59 enrolled patients, 50 patients underwent surgery and were assessable for the primary endpoint. R0‐resection rate was 86.0% (43/50). Pathologic complete response (pCR) was 20.0% (10/50) and a further 20% (10/50) of patients achieved near complete histological remission (<10% residual tumor). Among these very good responders, 85% (17/20) had intestinal type tumors, 10% (2/20) had diffuse and 5% (1/20) had mixed type tumors. After 3 cycles of NACT, 6.9% (4/58) of patients developed progressive disease. Median disease‐free survival was 32.9 months. The 1‐year survival‐rate was 79.3%. Grade 3‐4 toxicities included neutropenia 29.3%, febrile neutropenia 1.7%, diarrhea 12.1% and mucositis 6.9%. This study indicates that intensified NACT with 6 cycles of FLOT is highly effective and tolerable in resectable GEC. Very good response (pCR and <10% residual tumor) was predominantly observed in patients with intestinal type tumors.